TOTAL FACTOR PRODUCTIVITY (TFP) OF PRODUCTIVE RESOURCES USED IN HOMESTEAD POULTRY BROILER FARMS IN NIGER STATE OF NIGERIA - Sadiq, sanusi mohammed (Journal of Agricultural Sciences (Belgrade), 2019)
ABSTRACT The present research measured the total factor productivity (TFP) of productive resources used in homestead poultry broiler farms in Niger State of Nigeria, using structured questionnaire complemented with interview schedule to collect cross-sectional data from a drawn sample size of 97 active broiler producers via multi-stage sampling design. The data analyses were performed using descriptive and inferential statistics. Findings from the study showed evidence of productive labour force in the enterprise, literate farming population with sustainable household size typical of African agrarian setting. The enterprise was found to be profitable in the studied area. Furthermore, findings showed that marginally above the sampling population were productive in the utilization of their input resources which may be due to technical awareness of the modern poultry management techniques in the studied area. Thereafter, it was observed that gender status, experience, capital source and operational capital were the factors undermining farmers TFP. Therefore, study recommended gender sensitization and the need for public private partnership synergy to explore the untapped potentials in this sub-sector in the studied as almost half of the farmers were found not to be productive in the utilization of their resources.